2010
DOI: 10.1007/s00405-010-1205-3
|View full text |Cite
|
Sign up to set email alerts
|

First-night-effect on polysomnographic respiratory sleep parameters in patients with sleep-disordered breathing and upper airway pathology

Abstract: The objective of this study is to test whether there is a difference between the polysomnographic (PSG) values of Apnea-hypopnea index (AHI), minimal oxygen saturation (SpO(2)), oxygen desaturation index (ODI) and arousal index recorded on two consecutive nights (so-called "first night effect") in patients with sleep-disordered breathing (SDB) and concomitant upper airway pathology. Retrospective case-control study of polysomnographical recordings of 130 patients (112 males, 18 females, age range 23-80 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…34,[129][130][131] There was a wide range of OSA severity within the populations included in the four studies (AHI range: 7-34). None of the studies included data on body position during the 2 nights of PSG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34,[129][130][131] There was a wide range of OSA severity within the populations included in the four studies (AHI range: 7-34). None of the studies included data on body position during the 2 nights of PSG.…”
Section: Discussionmentioning
confidence: 99%
“…131 Only one of the studies indicated that PSG scorers were blinded to the other PSG result. ahi (niGht-to-niGht variaBility): A meta-analysis of four studies compared AHI data between 2 consecutive nights of PSG 34,[129][130][131] (see supplemental material, Figure S28 and Table S66) and found the mean difference in the AHI between the 2 nights was 0.14 (95% CI: −1.86 to 2.15), which was not statistically or clinically significant. Nonetheless, a subset of individuals had considerable night-to-night variability in their AHIs, which could have potential clinical implications if the AHI crosses a treatment threshold only during the second PSG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In consequence, concern about a potential "first-night effect" might be raised regarding the effectiveness for apnea severity. Based on the fact that several studies have uniformly reported no firstnight effect on respiratory parameters [14][15][16], it has been considered that the improvement of apnea severity with the iNAP ® device is not likely to be due to the first-night effect. However, the amelioration of WASO with the iNAP ® device might be due to the first-night effect.…”
Section: Discussionmentioning
confidence: 99%
“…With chronic therapy, improvements in these measures and further improvements in stage-shifts and awakenings and in daytime symptoms such as excessive daytime sleepiness can be anticipated but should be confirmed directly by future studies. In each subject, the sequence of PSG studies was not randomized and the baseline study was completed before the PSG with OPT; however, order of PSG evaluation is unlikely to have any significant effect on respiratory parameters 13. Moving beyond this feasibility study, in future studies, a randomized sequence of treatment conditions on PSG nights may be employed.…”
Section: Discussionmentioning
confidence: 99%